The “Habitat Provision” Index for Assessing Floodplain Biodiversity and Restoration Potential as an Ecosystem Service—Method and Application - Fischer, Christine; Damm, Christian; Foeckler, Francis; Gelhaus, Marion; Gerstner, Lars; Harris, Rebecca M. B.; Hoffmann, Tim G.; Iwanowski, Janette; Kasperidus, Hans; Mehl, Dietmar; Podschun, Simone A.; Rumm, Andrea; et al. (Frontiers in Ecology and Evolution, 2019)
River floodplains provide a large number of ecosystem services (ESS) for human societies. However, human manipulations of rivers and floodplains have led to the loss of many ecosystem services, including the provision of habitats for typical floodplain flora and fauna. To quantify such losses, we present a new index, which incorporates the functional and structural quality of riverine and alluvial habitats and their communities. The assessment is based on publicly available biotic and abiotic data at a local scale (e.g. habitat type mapping, species data). The new evaluation method consists of three steps: First, an evaluation at habitat type level is done by using well established assessment criteria (e.g. groundwater dependence, legal protection status, regenerability). Secondly the individual habitats are assessed based on specific quality characteristics (e.g. presence of protected birds or backwater influence). Finally, these values are aggregated within 1km floodplain compartments weighted by their spatial expansion. The index uses a five step value to describe the importance of a floodplain area for typical species and habitats from "very high" (= 5) to "very low" (= 1). The aim of this “habitat provision index” is to provide a tool for planners and decision makers to compare and analyze the effects of past or future measures. The methodical approach is tested for two rivers the Nahe and the Rhine. The performance of the index is analyzed by comparing the current conditions (status quo) against two different scenarios. The index is validated and shown to be sensitive to different water management scenarios (river restoration and technical polder scenario for flood risk enhancement), with both scenarios showing an improvement in the habitat provision value.